Keragaman Fenotipik dan Pendugaan Jarak Genetik pada Ayam Lokal dan Ayam Broiler Menggunakan Analisis Morfologi (PHENOTYPIC VARIATION AND ESTIMATION GENETIC DISTANCE BETWEEN LOCAL CHICKEN AND BROILER CHICKEN USING MORPHOLOGICAL ANALYSIS) - Mariandayani, Harini Nurcahya; Solihin, Dedy Duryadi; Sulandari, Sri; Sumantri, Cece (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
This aim of the research was to study the morphological characteristic and estimating genetic distancebetween local chicken and broiler chicken with discriminant and canonical analysis. This research washeld in Faculty of Animal Husbandry, Bogor Agricultural University, using 25 sentul chickens,  25  kampongchickens, 25 kedu chickens , 25  pelung chickens and 25 broiler chickens. The variable as the length ofshank, beak length, back length, chest depth and chest width were measured in this study. The collecteddata were analyzed by using SAS  and SPSS package program. Kampung chickens were mixed with sentulchickens (17.60 %) and kedu chickens (17,70 %). Kedu, kampong,  and  sentul chickens have a relativelyclose genetic distance   compared the genetic distance to pelung chickens with the kampung, sentul, andkedu chickens. Fenogram tree show that there were three separate groups of chickens at the age of eightweeks i.e. : (1) pelung chickens (2), kedu, kampong, and sentul chickens, (3) broiler chickens.  Fenogram treealso shows two separate groups : (1) pelung chickens (2) kedu, kampong, and Sentul chickens (at the age of28 weeks chicken).  The crossbreed between kedu and sentul chickens, also have a relatively close geneticdistance. The phenotypic size of  chickens giving a strong influence on the distinction variable of chickengroups were body length and chest circumference.
Keywords: local chicken, genetic distance, discriminant analysis, canonical